Nickel-calcium-based bifunctional material for coupling quenching process as well as preparation and application of nickel-calcium-based bifunctional material

The preparation of nickel-calcium-based bifunctional materials through coupled quenching process solves the problems of easy sintering and carbon deposition of existing materials during CO2 capture and methane dry reforming, and achieves efficient CO2 capture and conversion, improving the material's anti-packetization Carbon performance and cycle stability have good industrial application value.

CN119259057APending Publication Date: 2025-01-07SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411636854.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing nickel-calcium-based bifunctional materials are prone to sintering and carbon deposition during the dry reforming of CO2 capture and methane, resulting in a decrease in CO2 capture capacity, low synthesis gas yield and inactivation of the material.

Method used

Coupled quenching technology to prepare nickel-calcium-based bifunctional materials. By complexing water-soluble nickel salts and calcium salts with citric acid solutions, calcining and reducing treatment, metal composite oxides with rich pore structure and strong interaction are formed to enhance the material's Carbon deposit resistance and CO2 capture and conversion ability.

Benefits of technology

It significantly improves the CO2 capture and conversion performance of nickel-calcium-based bifunctional materials, enhances the resistance to carbon deposition, maintains efficient capture and conversion performance in multiple cycles, and has excellent gas transfer capabilities and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005137337740000011
    Figure HDA0005137337740000011
  • Figure HDA0005137337740000012
    Figure HDA0005137337740000012
  • Figure HDA0005137337740000021
    Figure HDA0005137337740000021
Patent Text Reader

Abstract

The invention discloses a nickel-calcium-based bifunctional material for a coupling quenching process as well as preparation and application of the nickel-calcium-based bifunctional material. Calcium oxide is used as a carrier, high-temperature calcium oxide is quenched in a mixed aqueous solution containing nickel nitrate, calcium nitrate and citric acid, the prepared nickel-calcium-based bifunctional material has excellent CO2 capture capacity and conversion capacity, a rich pore structure is created for the material through the quenching technology, the strong interaction between metal and the carrier is improved, and the CO2 capture capacity and conversion capacity of the material are improved. The active metal of the material is uniformly dispersed, the material has good CO2 conversion capability and carbon deposition resistance, and efficient integration of CO2 capture and synthesis gas preparation through in-situ methane dry reforming is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of CO2 capture and utilization, and specifically relates to a nickel-calcium-based dual-functional material for integrating CO2 capture and in-situ methane dry reforming to produce synthesis gas, and a preparation method and application thereof. Background Art

[0002] With the acceleration of global industrialization, the consumption and utilization of traditional fossil energy will lead to a sharp increase in the emission of greenhouse gas CO2. Excessive emission of CO2 has caused the deterioration of the global climate, which is the main cause of the greenhouse effect. Global warming and extreme weather caused by large-scale CO2 emissions have attracted the attention of countries around the world, and reducing carbon dioxide emissions has become a general trend.

[0003] Among them, integrated carbon dioxide capture and utilization (ICCU) technology is a solution that can effectively reduce carbon dioxide emissions and realize carbon dioxide conversion. This technology can not only capture and utilize CO2, but also solve the environmental problems caused by excessive CO2 emissions; at the same time, the generated syngas can be further converted into high value-added products. Therefore, ICCU technology has become a hot topic in current research. ICCU technology can realize carbon dioxide capture and in-situ methane dry reforming to prepare syngas under isothermal conditions, reducing the temperature or pressure change steps in traditional carbon capture technology, improving reaction efficiency, and helping to reduce carbon emissions. It is of great environmental and economic significance. This technology uses nickel-calcium-based bifunctional materials (DFMs) for calcium chain-coupled methane dry reforming. The calcium-based absorbent (i.e., CaO) captures CO2 to generate CaCO3. Subsequently, under isothermal conditions, CaCO3 reacts with CH4 for methane dry reforming under the action of a Ni-based catalyst to generate CO and H2 syngas, and regenerate the calcium-based absorbent.

[0004] The key to integrated carbon dioxide capture and utilization technology lies in the preparation of dual-functional materials (DFMs) with good performance and high economic benefits. CaO is low-cost and has a high CO2 adsorption capacity, and Ni-based catalysts are abundant and have good catalytic activity. However, due to side reactions between reactants and products, DFMs have problems such as easy sintering and carbon deposition during continuous cyclic reactions, resulting in reduced CO2 capture capacity, low syngas yield, and even material deactivation. Therefore, it is necessary to improve the structure of DFMs by optimizing or exploring new DFMs preparation methods to improve application performance. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a nickel-calcium based dual-functional material with a coupled quenching process.

[0006] By preparing DFMs using the quenching method, the synergistic effect between Ni and CaO is improved, and the structure of DFMs is improved, thereby enhancing the anti-carbon deposition properties of DFMs and improving the CO2 capture and conversion performance of dual-functional materials.

[0007] Another object of the present invention is to provide a nickel-calcium based dual-functional material with a coupled quenching process obtained by the above preparation method.

[0008] Another object of the present invention is to provide the application of the above-mentioned nickel-calcium-based dual-functional material with coupled quenching process in integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas. The object of the present invention is achieved by the following technical solutions:

[0009] A method for preparing a nickel-calcium-based dual-functional material by a coupled quenching process comprises the following steps:

[0010] (1) uniformly mixing a water-soluble nickel salt, a water-soluble calcium salt and water, and then adding a citric acid solution for complexation to obtain a metal precursor solution;

[0011] (2) calcining calcium oxide at 700-900° C. for 30-90 min and rapidly quenching it in a metal precursor solution, mixing it evenly, and drying it to obtain a nickel-calcium-based precursor;

[0012] (3) calcining a nickel-calcium-based precursor to obtain a metal composite oxide;

[0013] (4) Reducing the metal composite oxide in a reducing atmosphere to obtain a dual-functional material integrating CO2 capture and conversion.

[0014] Preferably, in the metal precursor solution of step (1), the molar ratio of total metal ions to citric acid is 1:1.5-2.5; more preferably 1:2.

[0015] Preferably, the molar ratio of calcium ions in the water-soluble calcium salt in step (1) to calcium oxide in step (2) is 1:1.7-4.5; more preferably 1:3.3.

[0016] Preferably, the molar ratio of the water-soluble nickel salt to the water-soluble calcium salt in step (1) is 1:1.3-4.0; more preferably 1:2.1.

[0017] Preferably, the water-soluble nickel salt in step (1) is at least one of nickel nitrate and nickel acetate; and the water-soluble calcium salt is at least one of calcium nitrate and calcium acetate.

[0018] Preferably, in step (1), the ratio of the water-soluble nickel salt to water is 0.01-0.05 mmol / ml, more preferably 0.03 mmol / ml; and the concentration of the citric acid solution is 0.2-0.6 mmol / ml, more preferably 0.4 mmol / ml.

[0019] Preferably, the calcination in step (2) is carried out in an air atmosphere.

[0020] Preferably, the heating rate of the calcination in step (2) is 2 to 15°C / min; more preferably 10°C / min.

[0021] Preferably, the rotation speed for uniform mixing in steps (1) and (2) is 300 to 500 r / min.

[0022] Preferably, the drying temperature in step (2) is 90 to 120° C. and the drying time is 36 to 60 hours.

[0023] Preferably, the drying in step (2) further requires grinding and sieving; more preferably, the sieving refers to sieving through an 80-mesh sieve.

[0024] Preferably, the calcination temperature in step (3) is 500-900° C. and the calcination time is 2-6 hours.

[0025] Preferably, the calcination in step (3) is carried out in an air atmosphere.

[0026] Preferably, the heating rate of the calcination in step (3) is 2 to 15°C / min; more preferably 10°C / min.

[0027] Preferably, the reducing atmosphere in step (4) is an atmosphere containing H2; more preferably, the reducing atmosphere has a volume concentration of 10% H2 / 90% N2.

[0028] Preferably, the flow rate of the reducing atmosphere in step (4) is 80 to 120 mL / min.

[0029] Preferably, the molar ratio of H2 to the metal composite oxide in the reducing atmosphere of step (4) is 22 to 92:1; more preferably 45.5:1.

[0030] Preferably, the reduction temperature in step (4) is 700-900°C.

[0031] Preferably, the reduction time in step (4) is 30 to 120 minutes.

[0032] The above preparation method obtains a nickel-calcium based dual-functional material with a coupled quenching process.

[0033] The above-mentioned nickel-calcium-based dual-functional material with a coupled quenching process is used in the integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas.

[0034] Preferably, the application is specifically as follows: adding the above-mentioned nickel-calcium-based bifunctional material with a coupled quenching process into a fuel reactor, first introducing an inert gas to purge the air in the fuel reactor, then heating the fuel reactor to the reaction temperature, introducing a mixed gas containing CO2, and after the capture of CO2 is completed, introducing an inert gas for purging, and then introducing a mixed gas of methane and protective gas to convert the CO2 captured by the material until no CO is produced in the reaction.

[0035] More preferably, the flow rate of the inert gas is 80-120 mL / min.

[0036] More preferably, the flow rate of the CO2-containing mixed gas is 80 to 120 mL / min.

[0037] More preferably, the molar ratio of CO2 to the nickel-calcium-based bifunctional material in the CO2-containing mixed gas is 0.7-4.0:1; the volume content of CO2 in the CO2-containing mixed gas is 5-15%; and most preferably 10%.

[0038] More preferably, the molar ratio of methane to the nickel-calcium-based bifunctional material is 0.5-2.0:1.

[0039] More preferably, the flow rate of the mixed gas of methane and protective gas is 80-120 mL / min.

[0040] More preferably, the volume ratio of methane to protective gas is 2:8 to 1:9.

[0041] More preferably, the reaction temperature is 550-725°C.

[0042] The present invention couples the quenching process with the preparation of nickel-calcium-based bifunctional materials, creating abundant pores to help capture CO2, while forming a strong interaction between the metal and the carrier. In the integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas, it has excellent CO2 conversion rate and anti-carbon deposition performance.

[0043] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0044] (1) The present invention adopts a quenching process to prepare a nickel-calcium-based bifunctional material. The bifunctional material prepared by this method has a rich pore structure, which creates a good gas transfer ability for the material and generates more oxygen vacancies, which promotes the adsorption and activation of CO2. The bifunctional material has excellent CO2 capture performance.

[0045] (2) The coupled quenching process of the present invention prepares a nickel-calcium-based metal composite oxide with uniformly dispersed active metals, which has a large number of dislocations and defects, and enhances the strong interaction between the metal and the carrier of the material, so that the bifunctional material can achieve efficient CO2 capture while having a suitable CO2 desorption rate and can react with methane for dry reforming in a timely manner, so that the bifunctional material has a higher CO2 conversion rate and can maintain good CO2 capture and conversion performance in multiple continuous cycles.

[0046] (3) In the present invention, the nickel-calcium-based bifunctional material obtained by partial reduction with a reducing gas is partially reduced. The partially reduced active metal promotes the transmission of lattice oxygen, which can effectively improve the anti-carbon deposition performance of the bifunctional material.

[0047] (4) The preparation method and application of the present invention are simple, and can realize CO2 capture and in-situ methane dry reforming to produce synthesis gas under isothermal conditions. It has excellent performance, low energy consumption, and good industrial application value and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 X-ray diffraction patterns of the nickel-calcium based dual-functional material coupled with 800°C quenching process obtained in Example 1 and the nickel-calcium based dual-functional material obtained by the sol-gel method in Comparative Example 1.

[0049] Figure 2 H2-TPR diagram of the nickel-calcium based bifunctional material coupled with 800°C quenching process obtained in Example 1 and the nickel-calcium based bifunctional material obtained by the sol-gel method in Comparative Example 1.

[0050] Figure 3 This is the microscopic morphology of the dual-functional material obtained in Example 1 through the coupled 800°C quenching process.

[0051] Figure 4 This is a diagram showing the reaction effect of the dual-functional material obtained in Example 1 coupled with an 800°C quenching process in integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas.

[0052] Figure 5 This is a diagram showing the reaction effect of the sol-gel dual-functional material obtained in Comparative Example 1 in integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas.

[0053] Figure 6 This is a diagram showing the reaction effect of the dual-functional material obtained in Example 2 coupled with a 700°C quenching process in integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas.

[0054] Figure 7 This is a diagram showing the reaction effect of the dual-functional material obtained in Example 3 coupled with a 900°C quenching process in integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas.

[0055] Figure 8 This is a diagram showing the reaction effect of the dual-functional material obtained in Comparative Example 2 coupled with a 300°C quenching process in integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas.

[0056] Fig. 9 This is a diagram showing the reaction effect of the dual-functional material obtained in Example 4 coupled with a 60-min quenching process in integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas.

[0057] Fig.10 This is a diagram showing the reaction effect of the dual-functional material obtained in Example 5 coupled with a 90-min quenching process in integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas. DETAILED DESCRIPTION

[0058] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0059] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0060] Example 1

[0061] (1) Preparation of nickel-calcium-based bifunctional materials coupled with quenching process: 5.17mmol nickel nitrate and 10.83mmol calcium nitrate were dissolved in 160ml deionized water, and then 80ml of a solution containing 32mmol citric acid was added for complexation to obtain a metal precursor solution. At the same time, 2g calcium oxide was calcined at 800℃ in an air atmosphere for 30min, and then the high-temperature calcium oxide was quickly poured into the prepared metal precursor solution, stirred after quenching, and placed in a 105℃ oven for 48h to obtain a nickel-calcium-based precursor. The dried sample was ground into powder and calcined in a muffle furnace at 800℃ in an air atmosphere for 4h, with a heating rate of 10℃ / min to obtain a metal composite oxide.

[0062] (2) The above-mentioned metal composite oxide is placed in a small fixed bed at 800°C, and 100 mL / min of 10% H2 / 90% N2 gas by volume is introduced for reduction for 60 minutes to obtain a dual-functional material with integrated CO2 capture and conversion coupled with an 800°C quenching process.

[0063] (3) Evaluation of CO2 capture characteristics of bifunctional materials: The integrated CO2 conversion and in-situ methane dry reforming to produce synthesis gas reaction were carried out in a small fixed bed. 0.3g of bifunctional material was placed in the center of a quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced at a rate of 100mL / min for 10min to exhaust the air. After the atmosphere furnace was heated to 700°C, the quartz tube was placed in the atmosphere furnace and the temperature was stabilized. Then the gas was switched to 100mL / min of CO2 (volume ratio 10% CO2 / 90% N2). The capture time in this stage was 21min. The synthesis gas obtained by the reaction was collected with a gas bag, and its composition was analyzed by gas chromatography. The CO2 capture amount of the bifunctional material in the reaction was 14.978mmol / g.

[0064] (4) Evaluation of CH4 conversion characteristics of bifunctional materials: After the CO2 capture stage, nitrogen was introduced at a rate of 100 mL / min for 5 minutes, and then the gas was switched to 100 mL / min CH4 (volume ratio 10% CH4 / 90% N2) until the reaction ended when no CO was generated. Similarly, the synthesis gas obtained by the reaction was collected with a gas bag and its composition was analyzed by gas chromatography. The CO2 conversion rate of the bifunctional material in the reaction reached 84.07%, the CH4 conversion rate was 63.35%, and the H2 to CO ratio was 1.345. The carbon deposition amount calculated by the carbon balance of the methane dry reforming reaction was only 1.418 mmol / g.

[0065] Comparative Example 1

[0066] (1) Preparation of nickel-calcium based bifunctional materials by sol-gel method: 5.17 mmol nickel nitrate, 46.53 mmol calcium nitrate and 32 mmol citric acid were dissolved in 40 ml deionized water and stirred at room temperature for 1 h. The solution was then placed in a 90 °C oil bath and stirred to evaporate until a viscous gel was formed. The solution was then placed in a 105 °C oven and dried for 48 h. The dried sample was ground into powder and calcined in a muffle furnace at 800 °C for 4 h in an air atmosphere with a heating rate of 10 °C / min to obtain a metal composite oxide.

[0067] (2) The above-mentioned metal composite oxide is placed in a small fixed bed at 800°C, and 100 mL / min of 10% H2 / 90% N2 gas by volume is introduced for reduction for 60 minutes to obtain a sol-gel dual-functional material integrating CO2 capture and conversion.

[0068] (3) Evaluation of CO2 capture characteristics of dual-functional materials: The integrated CO2 conversion and in-situ methane dry reforming to produce synthesis gas reaction were carried out in a small fixed bed. 0.3g of dual-functional material was placed in the center of a quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced at a rate of 100mL / min for 10min to exhaust the air. After the atmosphere furnace was heated to 700°C, the quartz tube was placed in the atmosphere furnace and the temperature was waited for to stabilize. Then the gas was switched to 100mL / min of CO2 (volume ratio 10% CO2 / 90% N2). The capture time in this stage was 21min. The synthesis gas obtained by the reaction was collected with a gas bag, and its composition was analyzed by gas chromatography. The CO2 capture amount of the dual-functional material in the reaction was 8.776mmol / g.

[0069] (4) Evaluation of CH4 conversion characteristics of bifunctional materials: After the CO2 capture stage, nitrogen was introduced at a rate of 100 mL / min for 5 minutes, and then the gas was switched to 100 mL / min CH4 (volume ratio 10% CH4 / 90% N2) until the reaction ended when no CO was generated. Similarly, the synthesis gas obtained by the reaction was collected with a gas bag and its composition was analyzed by gas chromatography. The CO2 conversion rate of the bifunctional material in the reaction was only 48.39%, and the carbon deposition amount was calculated by the carbon balance of the methane dry reforming reaction to be 2.553 mmol / g.

[0070] Example 2

[0071] The bifunctional material was prepared by the method of Reference Example 1, except that in step (1), 2 g of calcium oxide was calcined at 700°C for 30 min in an air atmosphere and then quenched, and step (2) obtained a bifunctional material with integrated CO2 capture and conversion coupled with a 700°C quenching process.

[0072] (3) Evaluation of CO2 capture characteristics of dual-functional materials: The integrated CO2 conversion and in-situ methane dry reforming reaction to produce synthesis gas was carried out in a small fixed bed. 0.3g of dual-functional material was placed in the center of a quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced at a rate of 100mL / min for 10min to exhaust the air. After the atmosphere furnace was heated to 700°C, the quartz tube was placed in the atmosphere furnace and the temperature was allowed to stabilize. The gas was then switched to 100mL / min of CO2 (volume ratio 10% CO2 / 90% N2). The capture time at this stage was 21min. The synthesis gas obtained by the reaction was collected with a gas bag, and its composition was analyzed by gas chromatography. The CO2 capture amount of the dual-functional material in the reaction was 13.199mmol / g.

[0073] (4) Evaluation of CH4 conversion characteristics of bifunctional materials: After the CO2 capture stage, nitrogen was introduced at a rate of 100 mL / min for 5 minutes, and then the gas was switched to 100 mL / min CH4 (volume ratio 10% CH4 / 90% N2) until the reaction ended when no CO was generated. Similarly, the synthesis gas obtained by the reaction was collected with a gas bag and its composition was analyzed by gas chromatography. The CO2 conversion rate of the bifunctional material in the reaction reached 79.79%, the CH4 conversion rate was 77.03%, the H2 to CO ratio was 1.388, and the carbon deposition amount was 1.574 mmol / g calculated by the carbon balance of the methane dry reforming reaction.

[0074] Example 3

[0075] The bifunctional material was prepared by the method of Example 1, except that in step (1), 2 g of calcium oxide was calcined at 900°C for 30 min in an air atmosphere and then quenched, and step (2) obtained a bifunctional material with integrated CO2 capture and conversion coupled with a 900°C quenching process.

[0076] (3) Evaluation of CO2 capture characteristics of bifunctional materials: The integrated CO2 conversion and in-situ methane dry reforming reaction to produce synthesis gas was carried out in a small fixed bed. 0.3g of bifunctional material was placed in the center of a quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced at a rate of 100mL / min for 10min to exhaust the air. After the atmosphere furnace was heated to 700°C, the quartz tube was placed in the atmosphere furnace and the temperature was allowed to stabilize. The gas was then switched to 100mL / min of CO2 (volume ratio 10% CO2 / 90% N2). The capture time at this stage was 21min. The synthesis gas obtained by the reaction was collected with a gas bag, and its composition was analyzed by gas chromatography. The CO2 capture amount of the bifunctional material in the reaction was 13.235mmol / g.

[0077] (4) Evaluation of CH4 conversion characteristics of bifunctional materials: After the CO2 capture stage, nitrogen was introduced at a rate of 100 mL / min for 5 minutes, and then the gas was switched to 100 mL / min CH4 (volume ratio 10% CH4 / 90% N2) until the reaction ended when no CO was generated. Similarly, the synthesis gas obtained by the reaction was collected with a gas bag and its composition was analyzed by gas chromatography. The CO2 conversion rate of the bifunctional material in the reaction reached 70.25%, the CH4 conversion rate was 80.27%, the H2 to CO ratio was 1.137, and the carbon deposition amount was 2.856 mmol / g using the carbon balance of the methane dry reforming reaction.

[0078] Comparative Example 2

[0079] The bifunctional material was prepared by the method of Reference Example 1, except that in step (1), 2 g of calcium oxide was calcined in an air atmosphere at 300°C for 30 min and then quenched, and step (2) obtained a bifunctional material with integrated CO2 capture and conversion coupled with a 300°C quenching process.

[0080] (3) Evaluation of CO2 capture characteristics of dual-functional materials: The integrated CO2 conversion and in-situ methane dry reforming reaction to produce synthesis gas was carried out in a small fixed bed. 0.3g of dual-functional material was placed in the center of a quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced at a rate of 100mL / min for 10min to exhaust the air. After the atmosphere furnace was heated to 700°C, the quartz tube was placed in the atmosphere furnace and the temperature was allowed to stabilize. The gas was then switched to 100mL / min of CO2 (volume ratio 10% CO2 / 90% N2). The capture time at this stage was 21min. The synthesis gas obtained by the reaction was collected with a gas bag, and its composition was analyzed by gas chromatography. The CO2 capture amount of the dual-functional material in the reaction was 12.733mmol / g.

[0081] (4) Evaluation of CH4 conversion characteristics of bifunctional materials: After the CO2 capture stage, nitrogen was introduced at a rate of 100 mL / min for 5 minutes, and then the gas was switched to 100 mL / min CH4 (volume ratio 10% CH4 / 90% N2) until the reaction ended when no CO was generated. Similarly, the synthesis gas obtained by the reaction was collected with a gas bag and its composition was analyzed by gas chromatography. The CO2 conversion rate of the bifunctional material in the reaction was only 67.17%, the CH4 conversion rate was 78.60%, and the ratio of H2 to CO was 1.651. The carbon deposition amount calculated by the carbon balance of the methane dry reforming reaction reached 3.885 mmol / g.

[0082] Example 4

[0083] (1) Preparation of nickel-calcium-based bifunctional materials coupled with quenching process: 5.17mmol nickel nitrate and 10.83mmol calcium nitrate were dissolved in 160ml deionized water, and then 80ml of a solution containing 32mmol citric acid was added for complexation to obtain a metal precursor solution. At the same time, 1g calcium oxide was calcined at 800℃ in an air atmosphere for 60min, and then the high-temperature calcium oxide was quickly poured into the prepared metal precursor solution, stirred after quenching, and placed in a 105℃ oven for 48h to obtain a nickel-calcium-based precursor. The dried sample was ground into powder and calcined in a muffle furnace at 800℃ in an air atmosphere for 4h, with a heating rate of 10℃ / min to obtain a metal composite oxide.

[0084] (2) The above-mentioned metal composite oxide is placed in a small fixed bed at 800°C, and 100 mL / min of 10% H2 / 90% N2 gas by volume is introduced for reduction for 60 minutes to obtain a dual-functional material with integrated CO2 capture and conversion coupled with a 60-minute quenching process.

[0085] (3) Evaluation of CO2 capture characteristics of dual-functional materials: The integrated CO2 conversion and in-situ methane dry reforming to produce synthesis gas reaction were carried out in a small fixed bed. 0.3g of dual-functional material was placed in the center of a quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced at a rate of 100mL / min for 10min to exhaust the air. After the atmosphere furnace was heated to 700°C, the quartz tube was placed in the atmosphere furnace and the temperature was waited for to stabilize. Then the gas was switched to 100mL / min of CO2 (volume ratio 10% CO2 / 90% N2). The capture time in this stage was 21min. The synthesis gas obtained by the reaction was collected with a gas bag, and its composition was analyzed by gas chromatography. The CO2 capture amount of the dual-functional material in the reaction was 11.059mmol / g.

[0086] (4) Evaluation of CH4 conversion characteristics of bifunctional materials: After the CO2 capture stage, nitrogen was introduced at a rate of 100 mL / min for 5 minutes, and then the gas was switched to 100 mL / min CH4 (volume ratio 10% CH4 / 90% N2) until the reaction ended when no CO was generated. Similarly, the synthesis gas obtained by the reaction was collected with a gas bag and its composition was analyzed by gas chromatography. The CO2 conversion rate of the bifunctional material in the reaction reached 90.27%, the CH4 conversion rate was 83.95%, and the ratio of H2 to CO was 1.607. The carbon deposition amount calculated by the carbon balance of the methane dry reforming reaction was only 0.525 mmol / g.

[0087] Example 5

[0088] (1) Preparation of nickel-calcium-based bifunctional materials by coupled quenching process: 5.17mmol nickel nitrate and 10.83mmol calcium nitrate were dissolved in 160ml deionized water, and then 80ml of a solution containing 32mmol citric acid was added for complexation to obtain a metal precursor solution. At the same time, 2.7g calcium oxide was calcined at 800℃ in an air atmosphere for 90min, and then the high-temperature calcium oxide was quickly poured into the prepared metal precursor solution, stirred after quenching, and placed in a 105℃ oven for 48h to obtain a nickel-calcium-based precursor. The dried sample was ground into powder and calcined in a muffle furnace at 800℃ in an air atmosphere for 4h, with a heating rate of 10℃ / min to obtain a metal composite oxide.

[0089] (2) The above-mentioned metal composite oxide is placed in a small fixed bed at 800°C, and 100 mL / min of 10% H2 / 90% N2 gas by volume is introduced for reduction for 60 minutes to obtain a dual-functional material with integrated CO2 capture and conversion coupled with a 90-minute quenching process.

[0090] (3) Evaluation of CO2 capture characteristics of dual-functional materials: The integrated CO2 conversion and in-situ methane dry reforming to produce synthesis gas reaction were carried out in a small fixed bed. 0.3g of dual-functional material was placed in the center of a quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced at a rate of 100mL / min for 10min to exhaust the air. After the atmosphere furnace was heated to 700°C, the quartz tube was placed in the atmosphere furnace and the temperature was allowed to stabilize. The gas was then switched to 100mL / min of CO2 (volume ratio 10% CO2 / 90% N2). The capture time at this stage was 21min. The synthesis gas obtained by the reaction was collected with a gas bag, and its composition was analyzed by gas chromatography. The CO2 capture amount of the dual-functional material in the reaction was 13.057mmol / g.

[0091] (4) Evaluation of CH4 conversion characteristics of bifunctional materials: After the CO2 capture stage, nitrogen was introduced at a rate of 100 mL / min for 5 minutes, and then the gas was switched to 100 mL / min CH4 (volume ratio 10% CH4 / 90% N2) until the reaction ended when no CO was generated. Similarly, the synthesis gas obtained by the reaction was collected with a gas bag and its composition was analyzed by gas chromatography. The CO2 conversion rate of the bifunctional material in the reaction reached 93.11%, the CH4 conversion rate was 51.35%, and the ratio of H2 to CO was 1.350. The carbon deposition amount calculated by the carbon balance of the methane dry reforming reaction was only 0.900 mmol / g.

[0092] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a nickel-calcium-based dual-functional material by a coupled quenching process, characterized in that: The following steps are involved: (1) uniformly mixing a water-soluble nickel salt, a water-soluble calcium salt and water, and then adding a citric acid solution for complexation to obtain a metal precursor solution; (2) calcining calcium oxide at 700-900° C. for 30-90 min and rapidly quenching it in a metal precursor solution, mixing it evenly, and drying it to obtain a nickel-calcium-based precursor; (3) calcining a nickel-calcium-based precursor to obtain a metal composite oxide; (4) Reducing the metal composite oxide in a reducing atmosphere to obtain a dual-functional material integrating CO2 capture and conversion.

2. The method for preparing a nickel-calcium-based dual-functional material by a coupled quenching process according to claim 1, characterized in that: The molar ratio of calcium ions in the water-soluble calcium salt in step (1) to calcium oxide in step (2) is 1:1.7-4.

5.

3. The method for preparing a nickel-calcium-based dual-functional material by a coupled quenching process according to claim 1, characterized in that: In the metal precursor solution of step (1), the molar ratio of total metal ions to citric acid is 1:1.5-2.5; The molar ratio of the water-soluble nickel salt to the water-soluble calcium salt in step (1) is 1:1.3-4.0; The water-soluble nickel salt in step (1) is at least one of nickel nitrate and nickel acetate; the water-soluble calcium salt is at least one of calcium nitrate and calcium acetate.

4. The method for preparing a nickel-calcium-based dual-functional material by a coupled quenching process according to claim 1, characterized in that: The calcination temperature in step (3) is 500-900° C. and the calcination time is 2-6 hours; The calcination in step (3) is carried out in an air atmosphere; The heating rate of the calcination in step (3) is 2 to 15°C / min.

5. The method for preparing a nickel-calcium-based dual-functional material by a coupled quenching process according to claim 1, characterized in that: The flow rate of the reducing atmosphere in step (4) is 80 to 120 mL / min; The reducing atmosphere in step (4) is an atmosphere containing H2; or the reducing atmosphere is a volume concentration of 10% H2 / 90% N2; The molar ratio of H2 to the metal composite oxide in the reducing atmosphere of step (4) is 22 to 92:1; The reduction temperature in step (4) is 700-900° C. The reduction time in step (4) is 30 to 120 minutes.

6. The method for preparing a nickel-calcium-based dual-functional material by a coupled quenching process according to claim 1, characterized in that: The calcination in step (2) is carried out in an air atmosphere; The heating rate of the calcination in step (2) is 2 to 15°C / min; In step (1), the ratio of the water-soluble nickel salt to water is 0.01-0.05 mmol / ml; and the concentration of the citric acid solution is 0.2-0.6 mmol / ml.

7. A nickel-calcium based dual-functional material prepared by a coupled quenching process according to the preparation method of any one of claims 1 to 6.

8. Application of the nickel-calcium-based dual-functional material with coupled quenching process as described in claim 7 in integrated CO2 capture and in-situ methane dry reforming to produce synthesis gas.

9. The use according to claim 8, characterized in that: The nickel-calcium-based bifunctional material with the above-mentioned coupled quenching process is added to the fuel reactor, and an inert gas is first introduced to clear the air in the fuel reactor. Then the fuel reactor is heated to the reaction temperature, and a mixed gas containing CO2 is introduced. After the CO2 is captured, an inert gas is introduced for purging, and then a mixed gas of methane and protective gas is introduced to convert the CO2 captured by the material until no CO is produced in the reaction.

10. The use according to claim 9, characterized in that: The molar ratio of CO2 to the nickel-calcium-based dual-functional material in the CO2-containing mixed gas is 0.7-4.0:1; the volume content of CO2 in the CO2-containing mixed gas is 5-15%; the flow rate of the CO2-containing mixed gas is 80-120 mL / min; The molar ratio of methane to nickel-calcium-based dual-functional material is 0.5-2.0:1; The volume ratio of methane to protective gas is 2:8 to 1:9; the flow rate of the mixed gas of methane and protective gas is 80 to 120 mL / min; The reaction temperature is 550-725°C.

Citation Information

Cited By

  • Multifunctional particles for calcium-based carbon dioxide capture and in-situ thermochemical conversion, preparation method, system and method

    CN121060535A